If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x in (-oo:+oo)
(7/9)*x = (6/2)/9 // - (6/2)/9
(7/9)*x-((6/2)/9) = 0
(7/9)*x-1/3 = 0
7/9*x-1/3 = 0 // + 1/3
7/9*x = 1/3 // : 7/9
x = 1/3/7/9
x = 3/7
x = 3/7
| 8x-2=-58+x | | -2=x-(-1) | | 1=b-8/2 | | 1x+1=2x+1 | | g-20/-2=0 | | 12xy^2-14x^3y^3-5y/2y^2 | | 3X-2=1/ | | 5243=49(p+40) | | -16=2(h+-13) | | 6-(2+3z)=-24 | | 10=3(s+1)+1 | | 5/13=t-16/3 | | -4=1-q | | 64n^2-9=0 | | 4(k+3)-(3k-5)=4 | | N/8=17 | | 1/2x-1=1/12x | | 7(x+8)=8+7x+14 | | 5x-3y=50 | | -2(-d-a)=3d+14 | | 9x-4x+120=9x+56 | | 742.61=2*3.14*256+2*3.14*r*16 | | 10x-17=10x-17 | | =-4-(6(2x-4)-6x) | | 0.25x=1228 | | 3x+2=12x-25 | | 1/3v-8/5=-3/2 | | 7x-12=11x-16 | | -4.6y+1.6=.6 | | -4.6+1.6=.6 | | 3x-7=-2x-5 | | 6x+19=11x-16 |